From Traditional Nanoparticles to Cluster-Triggered Emission Polymers for the Generation of Smart Nanotheranostics in Cancer Treatment - Cristina Blasco-Navarro; Carlos Alonso-Moreno; Iván Bravo (Journal of Nanotheranostics)
Nanotheranostics integrates diagnostic and therapeutic functionalities using nanoscale materials, advancing personalized medicine by enhancing treatment precision and reducing adverse effects. Key materials for nanotheranostics include metallic nanoparticles, quantum dots, carbon dots, lipid nanoparticles and polymer-based nanocarriers, each offering unique benefits alongside specific challenges. Polymer-based nanocarriers, including hybrid and superparamagnetic nanoparticles, improve stability and functionality but are complex to manufacture. Polymeric nanoparticles with aggregation-induced emission (AIE) present promising theranostic potential for cancer detection and treatment. However, challenges such as translating the AIE concept to living systems, addressing toxicity concerns, overcoming deep-tissue imaging limitations, or ensuring biocompatibility remain to be resolved. Recently, cluster-triggered emission (CTE) polymers have emerged as innovative materials in nanotheranostics, offering enhanced fluorescence and biocompatibility. These polymers exhibit increased fluorescence intensity upon aggregation, making them highly sensitive for imaging and therapeutic applications. CTE nanoparticles, crafted from biodegradable polymers, represent a safer alternative to traditional nanotheranostics that rely on embedding conventional fluorophores or metal-based agents. This advancement significantly reduces potential toxicity while enhancing biocompatibility. The intrinsic fluorescence allows real-time monitoring of drug distribution and activity, optimizing therapeutic efficacy. Despite their potential, these systems face challenges such as maintaining stability under physiological conditions and addressing the need for comprehensive safety and efficacy studies to meet clinical and regulatory standards. Nevertheless, their unique properties position CTE nanoparticles as promising candidates for advancing theranostic strategies in personalized medicine, bridging diagnostic and therapeutic functionalities in innovative ways.